A new biomarker to examine the role of hippocampal function in the development of spatial reorientation in children: a review - Vieites, Vanessa; Nazareth, Alina; Reeb-Sutherland, Bethany C.; Pruden, Shannon M. (Frontiers in Psychology, 2015)
Spatial navigation is an adaptive skill that involves determining the route to a particular goal or location, and then travelling that path. A major component of spatial navigation is spatial reorientation, or the ability to reestablish a sense of direction after being disoriented. The hippocampus is known to be critical for navigating, and has more recently been implicated in reorienting in adults, but relatively little is known about the development of the hippocampus in relation to these large-scale spatial abilities in children. It has been established that, compared to school-aged children, preschool children tend to perform poorly on certain spatial reorientation tasks, suggesting that their hippocampi may not be mature enough to process the demands of such a task. Currently, common techniques used to examine underlying brain activity, such as electroencephalography (EEG) and functional magnetic resonance imaging (fMRI), are not suitable for examining hippocampal development in young children. In the present paper, we argue for the use of eyeblink conditioning (EBC), a relatively under-utilized, inexpensive, and safe method that is easy to implement in developing populations. In addition, EBC has a well defined neural circuitry, which includes the hippocampus, making it an ideal tool to indirectly measure hippocampal functioning in young children. In this review, we will evaluate the literature on EBC and its relation to hippocampal development, and discuss the possibility of using EBC as an objective measure of associative learning in relation to large-scale spatial skills. We support the use of EBC as a way to indirectly access hippocampal function in typical and atypical populations in order to characterize the neural substrates associated with the development of spatial reorientation abilities in early childhood. Thus, we advocate for EBC as a simple biomarker for success in various tasks that require the hippocampus, including spatial reorientation.